Analisis Penyebab Nilai Yang Rendah Terhadap Peserta Didik di SMPN13 Medan - Sarah Lestari Tampubolon; Unedo Sinaga; Abdi Fristo Hutasoit (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Educational goals are goals to be achieved through comprehensive educational efforts. In the educational process at school, learning activities are the most basic activities. This means that the success or failure of achieving educational goals depends a lot on how the learning process is experienced by students as students. Processes are activities carried out by students to achieve teaching goals, while learning outcomes or better known as achievements are the abilities that students have after receiving their learning experience. This research aims to find out what causes the low assignment scores of students at SMPN 13 MEDAN. The method we use is qualitative research, where this research requires going directly into the field and requires clear factual data by relying on several sources of informants to confirm the previous analysis.